Pengaruh Pendidikan, Pelatihan, dan Mutasi Terhadap Kinerja Pegawai Negeri Sipil Pada Sekretariat Daerah Kabupaten Sinjai - Yusmanto, A.P.M; Nurwanah, N. (Journal of Management Sains (JMS), 2023)
The results of this study indicate that all the variables , namely : Education , Training , And Movements , have a positive and significant effect simultaneously on the performance of Civil Servants On the Regional Secretariat of Sinjai . Being partially found that training factors that have a significant influence most dominant performance of Civil Servants On Regional Secretariat Sinjai.